Analysis of the relationship between maternal-infant indicators and apgar score in the northern extreme of the Brazilian Amazon - Andrade, Lívia B. de; Dantas, Milton V. F.; Jesus, Dkaion V. de; Figuêiredo, Adelma A. de (Revista Saúde & Diversidade, 2018)
Introduction: The Apgar score evaluate the vitality of newborns. The Born Alive Declaration (BAD) is a questionnaire with the purpose of showing the distribution of clinical and epidemiological variables. Objective: To evaluate the association between variables in the Health Ministry's BAD and low Apgar score. Methods: It is a retrospective transversal study where data from 39.408 BAD from January 1st, 2008 to December, 31st 2012 in Roraima's public maternity hospital were analyzed. The statistical analysis used the chi-square method to compare differences between proportions of categorical variables. RR and CI95% were calculated under univariated analysis. The data were tabled and analyzed using the Epi Info® 7.0 version software. Results:Among the most associated factors to low Apgar at birth are: women above 20 years old (RR 1.69; CI95%: 1.34 – 2.13), first time mothers (RR 1.44, CI 95% 1.29 – 1.60, p<0.05), pregnant women who didn't had pre-natal care (RR 1.41, CI 95% 1.25 a 1.60, p <0.001), male newborns, newborns weighting less than 1.499g (RR 6.51, CI 95% 1.79 – 2.23), children born with gestational age (GA) smaller than 31 weeks, and GA from 32 to 36 weeks (RR 1.63, CI 95% 1.49 – 1.79). Conclusion: The BAD has proven to be a great instrument in evaluating Apgar and apprehending its risk factors. As expected, the age extremes, prematurity and insufficient pre-natal consults are related to low Apgar on the first minute. But, surprisingly, poorly educated mother didn't appear to be related to low Apgar score. We believe that it's necessary to better stratificate maternal age levels.